Synthesis of some 2-azitidinones (β-lactams) as antibiotic mimics and screening of their antimicrobial activity (Journal of Bangladesh Academy of Sciences, 2024)
2-Azetidinones (β-lactams) possess broad and potent bioactivity owing to the presence of lactam rings. As evidence has shown, it is one of the most critical biological frameworks. Some new 2- azetidinones have been synthesized from corresponding Schiff bases using different amines and aldehydes. All compounds (Schiff bases and β- lactams) were synthesized for comparison research using conventional and microwave techniques. The microwave approach has been found to reduce reaction time and boost yield drastically. Analysis combining elemental (C, H, and N) and spectroscopic approaches (NMR, IR, and UV) have been applied to ensure the Schiff bases constitution and corresponding β-lactams constitution. The newly synthesized compound's antibacterial action was estimated opposite to one gram-positive and one gram-negative bacteria. One compound (A-03) among synthesized 2-azitidinones was shown significant activity against the gram-positive bacteria. The other synthesized compounds had no substantial activity on either of the microorganisms.J. Bangladesh Acad. Sci. 48(1); 111-119: June 2024